2019
DOI: 10.4049/jimmunol.1801545
|View full text |Cite
|
Sign up to set email alerts
|

Self versus Nonself Discrimination by the Soluble Complement Regulators Factor H and FHL-1

Abstract: The plasma proteins Factor H (FH) and its alternate splice variant FH-like protein 1 (FHL-1) are the major regulators of the complement alternative pathway. The indiscriminate nature of alternative pathway activation necessitates the regulators to be host selective, but the underlying principles of selectivity remained largely elusive. By analyzing human FH and FHL-1 for protection of different host and foreign cells (rabbit and yeast), we uncovered a 2-fold discriminatory mechanism of FH in favor of self: rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 65 publications
3
49
3
Order By: Relevance
“…3E and 3F ). This is consistent with data of others (12, 24, 25) and probably due to complete consumption of C3 in the FH depleted serum. Addition of physiological pdFH concentrations partly restores the C3 deposition to NPS control situation ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…3E and 3F ). This is consistent with data of others (12, 24, 25) and probably due to complete consumption of C3 in the FH depleted serum. Addition of physiological pdFH concentrations partly restores the C3 deposition to NPS control situation ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Mutations R1210C, V1197A and G1194D result in destabilization of the tertiary structure (29), while V1197 is also shown to be important for binding to sialic acid (36). However, it is also noted that other ligands might have differential interactions in this binding region, such as heparin sulphates compared to sialic acid (36, 37) and is explained by the various effector functions of FH on different cells types, such as endothelial cells, glomerular membrane, retinal pigment epithelium, Bruch’s membrane in the eye, platelets or erythrocytes (24, 37, 38). A dual interaction of FH to C3b and sialic acid residues is crucial for protection of cells against unwanted complement activation on human cell surfaces (38).…”
Section: Discussionmentioning
confidence: 99%
“…On host-like sheep erythrocytes only FH CCPs 19-20 (carrying sialic acid and GAG binding properties), but not FH CCPs 6-8 (entailing only GAG binding functionality) exhibited functional competition with FH (24). A direct analysis of FH and FHL-1 regulatory capacity and surface specificity (host versus foreign) in FH/FHL-1-depleted serum revealed that both regulators protect foreign cell surfaces from complement attack at high concentrations, but FH was significantly more efficient in differentiating between foreign and host surfaces known to contain sialic acid moieties (14). This is in agreement with previous reports showing increased FH binding to sialylated surfaces (30,31).…”
Section: Molecular Insights Into the Regulatory Activity Of Fhl-1 Inmentioning
confidence: 95%
“…Similar to C3b binding, the successive addition of CCP domains to CCP1-4 enhanced the activity, while the addition of CCP6 to CCP1-5 had the largest impact on overall regulatory function (14,35,36). However, already in the fluid phase, when sialic acid binding does not even have a role in direct comparison to FH, FHL-1 appears to be a significantly weaker cofactor for Factor Imediated C3b degradation (13,14). Remarkably, this is also observed for the engineered versions of FH like miniFH.…”
Section: Molecular Insights Into the Regulatory Activity Of Fhl-1 Inmentioning
confidence: 98%
See 1 more Smart Citation